An overview of mini systematic literature on factors that influence the parents "perspective of leaving their children to / from school - A. Khalifa, Nasradeen (Penerbit UTHM, 2021)
The first walk to school program was in 1997, with just five primary schools taking part in Hertfordshire. Walk to School Day began in the United States of America (USA). as a one-day event. The first-ever International Walk to School Day launched in 2000. Today the International Walk to school day is celebrated in more than 40 countries and in thousands of schools across the United States of America (USA). The programs were extended to Canada, United Kingdom (UK), United States of America (USA), Ireland, Cyprus, and Gibraltar [1]. In 2003 the International Walk to School Day extended to become a week of activities in 33 countries including the United States of America (USA), Belgium, Canada, Australia, and New Zealand supported the activities. In 2006 the first International Walk to School Month was launched [2]. Every October, Victoria primary school encourages kids to walk, ride or scoot to and from school, local councils and communities are also encouraged to make active travel easy, safe, and accessible. Currently, 759 primary schools across Victoria take part in Walk to School, with 140,303 primary school kids walking more than 1.6 million kilometres during October, the equivalent of walking two return trips to the moon [3].